Amniotic fluid calreticulin in pregnancies complicated by the preterm prelabor rupture of membranes. (16th December 2016) - Musilova, Ivana; Andrys, Ctirad; Drahosova, Marcela; Soucek, Ondrej; Kutova, Radka; Pliskova, Lenka; Spacek, Richard; Laudanski, Piotr; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective : This study aimed to determine the amniotic fluid calreticulin concentrations in women with the preterm prelabor rupture of membranes (PPROM) based on the microbial invasion of the amniotic cavity (MIAC), intraamniotic inflammation (IAI) and microbial-associated IAI. Methods : One hundred sixty-eight women with singleton pregnancies were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis and were assayed for calreticulin concentrations by ELISA. IAI was defined as an amniotic fluid interleukin-6 concentration > 745 pg/ml. Microbial-associated IAI was defined as the presence of both MIAC and IAI. Result : Women with MIAC (with MIAC: median 54.4 ng/ml, versus without MIAC: median 32.6 ng/ml; p  <   0.0001), IAI (with IAI: median 66.8 ng/ml, versus without IAI: median 33.0 ng/ml; p  <   0.0001) and microbial-associated IAI (with microbial-associated IAI: median 82.5 ng/ml, versus without microbial-associated IAI: median 33.7 ng/ml; p  <   0.0001) had higher concentrations of calreticulin than women without these complications. An amniotic fluid calreticulin concentration of 81.4 ng/ml was found to be the best cutoff point for identifying women with microbial-associated IAI. Conclusions : The presence of microbial-associated IAI is associated with increased amniotic fluid calreticulin concentrations. Calreticulin seems to be a promising marker for the early identification of PPROM complicated by microbial-associated IAI.